Integrasi Role-Based Access Control dan First In First Out pada Sistem Point of Sales Berbasis Android untuk Optimalisasi Pengelolaan Transaksi dan Inventori UMKM Bengkel - Lilo Puji Pratama; Damar Nurcahyono; Muhammad Farman Andrijasa (JSAI (Journal Scientific and Applied Informatics), 2026)
This study aims to develop an Android-based Point of Sales (POS) system to improve transaction and inventory management in automotive repair shop SMEs. The main problem identified was that transaction recording and inventory management were still performed manually, resulting in delays and inventory data inconsistencies. The research employed the Waterfall method, which includes requirement analysis, system design, implementation, testing, and system evaluation stages. The system was developed using Kotlin and Firebase Realtime Database by implementing Role-Based Access Control (RBAC) for user access security and the First In First Out (FIFO) method for inventory management. System evaluation was conducted using black-box testing, System Usability Scale (SUS), operational efficiency analysis, and security testing. The results showed that all system features functioned properly. Usability evaluation involving 40 respondents through Google Forms obtained an SUS score of 82.5%, categorized as “Excellent.” The system also improved operational efficiency by reducing transaction recording time by 80% and increasing item search speed by 83% compared to the manual method. The implementation of RBAC and FIFO successfully improved access security and inventory management consistency in automotive repair shop SMEs.